Performance of Screening Ultrasonography as an Adjunct to Screening Mammography in Women Across the Spectrum of Breast Cancer Risk - Lee, Janie M; Arao, Robert F; Sprague, Brian L; Kerlikowske, Karla; Lehman, Constance D; Smith, Robert A; Henderson, Louise M; Rauscher, Garth H; Miglioretti, Diana L (JAMA internal medicine, 2019)
Whole-breast ultrasonography has been advocated to supplement screening mammography to improve outcomes in women with dense breasts. To determine the performance of screening mammography plus screening ultrasonography compared with screening mammography alone in community practice. Observational cohort study. Two Breast Cancer Surveillance Consortium registries provided prospectively collected data on screening mammography with vs without same-day breast ultrasonography from January 1, 2000, to December 31, 2013. The dates of analysis were March 2014 to December 2018. A total of 6081 screening mammography plus same-day screening ultrasonography examinations in 3386 women were propensity score matched 1:5 to 30 062 screening mammograms without screening ultrasonography in 15 176 women from a sample of 113 293 mammograms. Exclusion criteria included a personal history of breast cancer and self-reported breast symptoms. Screening mammography with vs without screening ultrasonography. Cancer detection rate and rates of interval cancer, false-positive biopsy recommendation, short-interval follow-up, and positive predictive value of biopsy recommendation were estimated and compared using log binomial regression. Screening mammography with vs without ultrasonography examinations was performed more often in women with dense breasts (74.3% [n = 4317 of 5810] vs 35.9% [n = 39 928 of 111 306] in the overall sample), in women who were younger than 50 years (49.7% [n = 3022 of 6081] vs 31.7% [n = 16 897 of 112 462]), and in women with a family history of breast cancer (42.9% [n = 2595 of 6055] vs 15.0% [n = 16 897 of 112 462]). While 21.4% (n = 1154 of 5392) of screening ultrasonography examinations were performed in women with high or very high (≥2.50%) Breast Cancer Surveillance Consortium 5-year risk scores, 53.6% (n = 2889 of 5392) had low or average (<1.67%) risk. Comparing mammography plus ultrasonography with mammography alone, the cancer detection rate was similar at 5.4 vs 5.5 per 1000 screens (adjusted relative risk [RR], 1.14; 95% CI, 0.76-1.68), as were interval cancer rates at 1.5 vs 1.9 per 1000 screens (RR, 0.67; 95% CI, 0.33-1.37). The false-positive biopsy rates were significantly higher at 52.0 vs 22.2 per 1000 screens (RR, 2.23; 95% CI, 1.93-2.58), as was short-interval follow-up at 3.9% vs 1.1% (RR, 3.10; 95% CI, 2.60-3.70). The positive predictive value of biopsy recommendation was significantly lower at 9.5% vs 21.4% (RR, 0.50; 95% CI, 0.35-0.71). In a relatively young population of women at low, intermediate, and high breast cancer risk, these results suggest that the benefits of supplemental ultrasonography screening may not outweigh associated harms.